LIANAS AND SHRUBS REGENERATION, DISTRIBUTION PATTERN AND DIVERSITY IN TROPICAL FOREST ECOSYSTEM OF CHHATTISGARH - M. K. JHARIYA; P. R. ORAON (The Bioscan, 2012)
Lianas are important components of tropical forests and have significant impacts on the diversity, structure and dynamics of tropical forests ecosystem, but may also have negative impacts on tree growth and productivity. The study censured lianas and shrubs in four sites (High, medium, low and non-fire zone) were selected; in each of these sites pre-fire and post-fire observation were taken for measuring different parameters. The density (Lianas and shrub) was varied from 1120 to 2480 individuals ha-1 during the pre-fire season and 1920 to 3360 individuals ha-1 at the time of post-fire season. The Shannon index values were varied from 2.35 to 3.13, equitability 1.28 to 1.37, species richness 0.71 to 1.17, concentration of dominance 0.12 to 0.22 and beta diversity 1.10 to 1.83 during pre-fire season. The total 11 species were recorded during pre-fire season whereas it had increase after the fire (20 species). Abundance to frequency ratio of the study indicated that the most of species showed contagious and random distribution pattern during pre-fire season while in the post-fire most of the species may distributed contagiously, few species were distributed randomly and regularly across the forest sites.